Conservación de la diversidad bio-cultural en Costa Rica: comunidades indígenas y el ambiente - Campregher, Christoph (2012)
Biodiversity hotspots are frequently inhabited by indigenous populations who have conserved unique ecoystems. This article reviews theoretical and empirical studies in Biocultural Diversity with an emphasis on the indigenous people of Costa Rica and with some preliminary insights of the author‘s fieldwork with the Ngäbe of Alto Laguna de Osa.